PERLINDUNGAN HUKUM BAGI TERTANGGUNG DALAM HAL TERJADI KEPAILITAN SUATU PERUSAHAAN ASURANSI - Cynthia Tungga Dewi, Anak Agung; Ari Yuliartini Griadhi, Ni Made (Kertha Semaya : Journal Ilmu Hukum; Vol. 02, No. 04, Juni 2014)
Legal protection of the insured in case of bankruptcy of the insurance company is absolutely necessary if an insolvent insurance company. It is intended that do not pose a concern for the insured to get their rights from the insurance company declared bankrupt. The research method adopted is that normative legal research is conducted legal research associated with written legal norms ie by examining the literature in the form of primary legal materials that legislation which in this case is Law No. 37 of 2004 on Bankruptcy and Suspension of Payment as well as Law No. 2 of 1992 on Insurance Business. From the research it can be stated that the law gives legal protection to the insured in the form of the appointment of a curator who perform the maintenance and settlement of the bankruptcy estate and the determination of the legal position of the insured policyholder based on the nature of the individual receivable, become preferred creditors, unsecured creditors, or creditors separatist.
Keywords: Bankruptcy, Insurance, Legal Protection, Insured